Cryogenic Differential Calorimetry: Exothermicity of Amorphous-to-crystalline Phase Transitions (ACPT) in Astrophysical and Cometary Ice Analogs - Rahul K. Kushwaha; Murthy S. Gudipati; Bryana L. Henderson (The Astrophysical Journal)
Amorphous ice is understood to be the predominant phase of water in cometary nuclei. A significant number of other volatiles can be trapped in amorphous H _2 O ice and released during the amorphous-to-crystalline phase transition (ACPT). This phase transition is an exothermic and is considered a potential cause of cometary outbursts, such as those observed in Comet 1P/Halley and Comet Hale–Bopp. However, only a single experimental study reported in the literature suggests that the presence of impurities (>2%) in amorphous H _2 O ice suppresses the exothermic effect and results in an endothermic phase transition, which contradicts the hypothesis of exothermic-phase-transition-driven comet outbursts. To further explore this phenomenon, we conducted experiments on pure H _2 O, CO:H _2 O, and CO _2 :H _2 O ice mixtures with varying fractions (11%, 50%, and 80% CO, and 11%, 25%, and 50% CO _2 , both relative to H _2 O (100%)). Our experimental setup is a highly sensitive cryogenic differential scanning calorimeter with a μ K noise floor and fifth-decimal resolution in temperature ratio of reference and ice. Our calorimetric data have been internally calibrated to ice sublimation endotherm to derive quantitative calorimetric data. We find that ACPT is exothermic in all CO:H _2 O mixtures and CO _2 :H _2 O mixtures with lower CO _2 fractions. In mixtures with the highest CO _2 content (50% relative to H _2 O (100%)) examined, the ACPT exotherm is weakened. Our results demonstrate that ACPT exothermicity persists throughout the CO and CO _2 mixing ratios observed in a majority of comets, and it should play an important role in comet outbursts when CO and CO _2 are the major volatiles trapped in amorphous H _2 O ice.